Reproducing kernel functions for the generalized Kuramoto-Sivashinsky equation - Akgul, Ali; Akgul, Esra Karatas; Korhan, Sahin; İnç, Mustafa (E D P Sciences, 2018)
Reproducing kernel functions are obtained for the solution of generalized Kuramoto Sivashinsky (GKS) equation in this paper. These reproducing kernel functions are valuable in the reproducing kernel Hilbert space method. They will be useful for interested researchers.
3rd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 04-06, 2018 -- Final Int Univ, Girne, CYPRUS
Keywords: Numerical-Solutions